Development of microwave cavities for measurement of muonium hyperfine structure at J-PARC. (23rd April 2021) - Tanaka, K S; Iwasaki, M; Kamigaito, O; Kanda, S; Kawamura, N; Matsuda, Y; Mibe, T; Nishimura, S; Saito, N; Sakamoto, N; Seo, S; Shimomura, K; et al.
Abstract: The MuSEUM collaboration is planning measurements of the ground-state hyperfine structure (HFS) of muonium at the Japan Proton Accelerator Research Complex (J-PARC), Materials and Life Science Experimental Facility. The high-intensity beam that will soon be available, the H-line, allows for more precise measurements by one order of magnitude. We plan to conduct two staged measurements. First, we will measure the Mu-HFS in a near-zero magnetic field, and thereafter we will measure it in a strong magnetic field. We have developed two microwave cavities for this purpose. Furthermore, we evaluated the systematic uncertainties from such a fluctuation of microwave fields and confirmed the requirements for the microwave system; we use a microwave field distribution calculated with the finite element method.